Indonesia: Impacts of COVID-19 on Production, Poverty and Food Systems - Pradesha, Angga; Syarifah, Amaliah; Noegroho, Anang; Thurlow, James (2020)
By Angga Pradesha, Amaliah Syarifah, Anang Noegroho, and James Thurlow